The Role of Friction and Tangential Compliance on the Resultant Launch Angle of a Golf Ball - Erik Henrikson; Paul Wood; Chris Broadie; Tom Nuttall (Proceedings, 2020)
A thorough understanding of how the delivered face angle and club path of a golf club influences the initial launch direction of a golf ball can play a significant role in the design of various club types as well as help players and coaches better understand performance in the field. A theoretical model based on a Hertzian impact formulation with the inclusion of tangential compliance via Coulomb friction is compared to empirical results. This comparison demonstrates that the initial launch direction of a golf ball for a given club path and face angle can be sufficiently predicted by the theoretical model, providing insights into the mechanisms leading to different launch direction percentages relative to face angle for various club types. Additionally, the relationship between launch direction and the coefficient of friction is explored for various angles of incidence.